Heat transfer study of a cold plate with fractal designs - Ow Yong, Daniel Zhao Yi (2018)
This project investigates the capability of heat transfer enhancement for fractal-like designs by single-phase forced convection using water experimentally. The condition of the experiment was held under constant heat flux. Design exploration was carried out using Computer Aided Design Software to develop two different categories of insert. The first category of two-dimensional inserts includes five different designs that were manufactured using Computer Numerical Control Milling Machine (Mazak FJV Machining Center). Due to time constraints, the three-dimensional insert were not manufactured. A new experiment rig was built and experimental investigations were carried out using the rig for the entire span of the project. A test on the reliability of the experiment rig was conducted using the numerical simulation software “COSMOL Multiphysics”. The results of the numerical simulation were compared with the experimental results of the bare cold plate. Subsequently, the experiments were conducted on 4 different cold plates from K = 1 to K = 4, denoting the level of bifurcation. These designs were compared with a cold plate of straight channels. The experiment was conducted in an open loop form with water flowing at a mass flow rate of 0.01 to 0.05 kg/s under constant heat flux condition. The results suggest that with the same volume of material used, the thermal performance of the fractal-like design (K = 4) has performed approximately 28% compared to that of the straight channel. The present investigation suggests that the increase in thermal performance is due to the bifurcation of branches. The bifurcation restarts the boundary layer development. When the flow is directed into multiple flow paths, the individual boundary layers restart from the bifurcated position enabling a higher heat transfer coefficient.